2019
DOI: 10.1101/557140
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic and genomic analyses reveal boundaries between species closely related to Cryptococcus pathogens

Abstract: Speciation is a central mechanism of biological diversification. While speciation is well studied in plants and animals, in comparison, relatively little is known about speciation in fungi.One fungal model is the Cryptococcus genus, which is best known for the pathogenic Cryptococcus neoformans/Cryptococcus gattii species complex that causes over 200,000 new infections in humans annually. The closest non-human pathogenic relatives are the sibling species, Cryptococcus amylolentus and Tsuchiyaea wingfieldii. Ho… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 106 publications
(129 reference statements)
1
20
0
Order By: Relevance
“…An instance of physically linked MAT loci has been well-studied in Cryptococcus neoformans, a member of a group of closely related, pathogenic Cryptococcus species [1]. Fusion of the HD and P/R loci most likely occurred in the ancestor of the pathogenic Cryptococci, because other analyzed Tremellales species including the closely related, but non-pathogenic Cryptococcus amylolentus, Kwoniella heveanensis, Kwoniella mangrovensis, Cryptococcus wingfieldii, and Cryptococcus floricola are all tetrapolar [33][34][35][36][37]. The C. neoformans MAT locus, which consists of genetically linked HD and P/R loci, encompasses more than 20 genes over a region spanning more than 100 kb and has two alleles designated a and α.…”
Section: Introductionmentioning
confidence: 99%
“…An instance of physically linked MAT loci has been well-studied in Cryptococcus neoformans, a member of a group of closely related, pathogenic Cryptococcus species [1]. Fusion of the HD and P/R loci most likely occurred in the ancestor of the pathogenic Cryptococci, because other analyzed Tremellales species including the closely related, but non-pathogenic Cryptococcus amylolentus, Kwoniella heveanensis, Kwoniella mangrovensis, Cryptococcus wingfieldii, and Cryptococcus floricola are all tetrapolar [33][34][35][36][37]. The C. neoformans MAT locus, which consists of genetically linked HD and P/R loci, encompasses more than 20 genes over a region spanning more than 100 kb and has two alleles designated a and α.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other basidiomycetes, the C. neoformans MAT locus is unusually large, spanning more than 100 kb and containing more than 20 genes. Studies have shown that the MAT locus in C. neoformans is a fusion product of the ancestral P/R and HD loci, and thus includes genes encoding both homeodomain transcription factors (HD), as well as pheromones and pheromone receptors (P/R) (LOFTUS et al 2005;HSUEH et al 2011;SUN et al 2017;PASSER et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Cryptococcus amylolentus, together with Cryptococcus floricola and Cryptococcus wingfieldii, are the most closely related known sibling species of the C. neoformans/C. gattii pathogenic species complex (FINDLEY et al 2009;PASSER et al 2019). C. amylolentus has a tetrapolar mating system with the two mating type loci (A and B) located on different chromosomes.…”
Section: Introductionmentioning
confidence: 99%
“…It is homothallic, self‐fertile fungal species with a continuously activated sexual cycle 18 . Divergence of pathogenic species from their non‐pathogenic ancestors is largely attributed to chromosomal alterations in the MAT loci, which are also the probable cause of the change from the tetrapolar sexual cycle in C. amylolentus and C. wingfieldii to the bipolar sexual cycle in pathogens 13,14,16,18 …”
Section: Sexual Reproductionmentioning
confidence: 99%